Predictors of Nebulized Arformoterol Treatment: A Retrospective Analysis of Medicare Beneficiaries with Chronic Obstructive Pulmonary Disease*. (4th March 2019) - Gilmer, Todd P.; Celli, Bartolome R.; Xu, Zhun; Cho-Reyes, Soojin; Dembek, Carole; Navaie, Maryam
Abstract: This study examined sociodemographic and clinical characteristics, treatment patterns, and health resource utilization among Medicare beneficiaries with chronic obstructive pulmonary disease (COPD) to identify predictors of nebulized arformoterol treatment. Using Medicare administrative data from 2010 to 2014, beneficiaries with ≥2 COPD outpatient visits ≥30 d apart or ≥1 COPD-related hospitalization(s) (ICD-9-CM 491.xx, 492.xx, and 496) were identified. Inclusion criteria required ≥1 COPD medication claim(s) and continuous enrollment in Parts A, B, and D. Four cohorts were identified: (a) 11, 887 arformoterol users, (b) a subsample of arformoterol users ( n =  1, 778) who were hospitalized and discharged 30 d before initiating arformoterol, (c) 450, 178 controls who had not received arformoterol, and (d) a subsample of controls ( n =  21, 910) who had hospitalizations. Logistic regression analysis was used to evaluate predictors of arformoterol treatment. The majority of beneficiaries were older than 70 years of age, female, Caucasian, and 47% were dual-eligible. The strongest predictors of arformoterol treatment were oxygen therapy, systemic corticosteroid or methylxanthine use, an exacerbation, a COPD-related hospitalization, and receiving care from a pulmonologist (all p  < .001). Dual-eligibility, being a racial/ethnic minority, and having severe psychiatric comorbidity or immunodeficiency lowered the odds of receiving nebulized arformoterol (all p  < .001). Among beneficiaries with recent hospitalizations, exacerbations and COPD-related admissions increased the odds of receiving arformoterol ( p  < .001). Nebulized arformoterol treatment was more likely to be initiated in sicker patients with COPD. Ensuring access to nebulized maintenance therapy is important and particularly warranted for COPD populations with greater medical needs.